Evisceração do intestino delgado através de perfuração de prolapso retal em uma criança - Martins,José Luiz (1998)
The rectal prolapse is very common in children under 3 years old. Rectal mucosae herniated in to the anal canal. The ethiologic causes are diarrhea, intestinal parasitosis, obstipation and desnutrition. The effort during the defecation, prolonged diarrhea and obstipation are important contribucting factors. The treatment in the majority of cases is medical treating factors like desnutrition, diarrheia and parasitosis. The authors report a case of a 3-month-old child with chronic diarrhea, severe desnutrition and recurrent rectal prolapse with perforation hole. This is a rare complication and considerations are made regarding the management of the case.